PENGAKUAN HAK MASYARAKAT ADAT ATAS TANAH ULAYAT: ANALISIS HUBUNGAN ANTARA HUKUM NASIONAL DAN HUKUM ADAT - Damianus Krismantoro (GoAcademica Research dan Publishing, 2022)
The purpose of this study is to analyze the relationship between national law and customary law on ulayat land. The type of research used is normative legal research. The legal approach used is conceptual type. The legal sources used are primary legal sources and secondary legal sources. The analysis and discussion used in this study uses a deductive framework. Based on the results of the analysis, it can be concluded that there is a relationship between state law and customary law in the agrarian and land law sectors, in practice there are still many that are not in accordance with the spirit of the nation, as well as the philosophy of national land law. The regulation on the determination of land rights which is only in the form of a certificate issued by the BPN has not been able to answer the expectations of the customary law community, because the policy has not regulated the mechanism for the protection of land law objects in the territory of the customary law community.